Does exogenous carbon source always promote algal biomass and nutrients removal in algal-bacterial wastewater remediation?. (25th January 2021) - Zhong, Yuming; Liu, Hui; Li, Huankai; Lu, Qian; Sun, Yan
Abstract: Glycerol is important to algal growth, but it is not necessarily right for all wastewater-borne bacteria, especially the beneficial bacterial flora or beneficial bacterium. This study focuses on the microalgal-bacterial community and interactive network analysis between algae and wastewater-borne bacteria to find beneficial bacteria, then identify the effect of glycerol on a beneficial bacterial strain. Microalgal-bacterial remediation shown better nutrients removal and microalgal biomass in centrate wastewater, and glycerol addition considerably increased biomass but inapparently increase nutrients removal. Pseudomonas sp. and Acinetobacter sp. dominated in algal-bacterial system with and without glycerol. Microbial community and environmental factors formed a linkage network in three cultural modes to find the most vital probiotic. The co-cultivation of microalgae and Pseudomonas aeruginosa as a non-fermentative denitrifying phosphate accumulating organism (DPAO) showed co-cultivation dramatically enhanced biomass yield and nutrients removal efficiencies, especially nitrogen and phosphorous. After adding glycerol, in the late stage of co-cultivation, algal-bacterial consortia collapsed, rendering the reduction of treatment efficiency and biomass. Non-fermentative bacteria as main probiotics in algal-based wastewater remediation were required to prepare small-molecule-weight organics as carbon sources. This study expects to optimize design and operation of algal-bacterial wastewater remediation that can be extended to similar carbon-deficit wastewaters simultaneously obtaining higher biomass and removal efficiency. Graphical abstract: Image 1 Highlights: Adding glycerol increased biomass and CFU but no nutrients removal. Microbial community and environmental factors formed a linkage network. A beneficial bacterial strain, Pseudomonas aeruginosa, was isolated and identified. Glycerol addition made algae-probiotic consortia collapse to reduce treatment efficiency and biomass. Relationship between algae and Pseudomonas sp. with/without glycerol was discussed.